Bio-Nanocomposite Polyurethane / Clay / Chitosan Paints that have thermal resistance and antibacterial properties for biomedical applications - T., Rihayat; Suryani, .; S., Riskina; J.P., Sirega; J., Jaafar; T., Cionita*; Fitria, . (IOP Publishing, 2020)
The coating material used for the manufacture of polyurethane paints is a coating of hybrid organic-inorganic materials based on palm oil (oleic acid). Polyols are produced from the synthesis of oleic acid by adding organic and inorganic ingredients. Chitosan and bentonite are organic and inorganic elements, which are used to improve thermal capability and antibacterial properties of polyurethane paint produced. Hybrid bentonite-chitosan is then synthesized with polyols and isocyanate is added, namely TDI (Toluene Diisocyanate) to form polyurethane. In the FTIR spectrum of the polyol on O-H bond at Wavelength 3210.25 cm-1, C-H bond at Wavelength 2856.87 cm-1 and C = O bond at Wavelength 1610.86 cm-1, and hybrid bentonitechitosan of FTIR Analysis Chitosan: -OH group at Wavelength 3250 cm-1, N-H at 3545 cm-1, C = O at wavelength 1681 cm-1, C-H group at Wavelength 2810 cm-1. Bentonite: -OH group at Wavelength 3435 cm-1, Si-O group at Wavelength of 1161 cm-1 and Al-O and Si-O groups at Wavelength 820 cm-1. Aliphatic C-H Cluster at 2815 cm-1 Wavelength and 1125 cm-1 Wavelength indicates the presence of a C-O group. While the results of SEM (Scanning Electron Microscope) from polyurethane products and with the addition of hybrid bentonite-chitosan namely polyurethane paints produced mixed with chemicals and the main ingredients are polyols from palm oil (oleic acid) while small white clumps greyish namely hybrid bentonite-chitosan which has been mixed into polyurethane paint. This study produced a hybrid material of benthicchitosan as a filler in the manufacture of polyurethane paint.